Building Collapse and Its Prevention in Lagos: The Role of Estate Surveyors and Valuers (International Journal of Scientific Research and Management (IJSRM), 2024)
Building collapse incidents in Nigeria appear to be on the increase with the cases witnessed in Lagos State being the worst. The situation has been endemic notwithstanding the efforts of professionals and other stakeholders in the built environment. Numerous literatures exist on the issue of building collapse. However, they mostly focus on the roles of other professionals such as Structural Engineers, Builders, Architects and Town Planners. On the contrary, this study centers on highlighting the significance of Estate Surveyors and Valuers contributions by getting their perspectives on building collapse , particularly in Lagos Island areas VI, Lekki, Lagos Island & Ikoyi) of Lagos State. The study employed a conceptual model which identified various factors responsible for building collapse in Lagos Island areas of Lagos, the major roles of Estate Surveyors and Valuers which can facilitate a significant reduction building collapse in Lagos State, the challenges faced by Estate Surveyors and Valuers in ensuring building collapse prevention in Lagos State and evaluated the effectiveness of existing regulations and guidelines governing the role of Estate Surveyors and Valuers in building collapse prevention in Lagos State. Data collection was by the administration of a well-structured questionnaire. Out of 80 copies of the questionnaire administered using Purposive Expert-Homogeneous sampling technique, 83.75% response rate were retrieved and evaluated for further analysis, with mean item score, and inferential statistics using Chi-square Test for the hypothesis test. The result indicates that Estate Surveyors and Valuers have significant impact in the prevention of building collapse. Based on the research findings, some useful recommendations were advanced.